Cross-Sectional Analysis of Complications in Patients Undergoing Primary vs. Revision Total Knee Arthroplasty - Rahul Bains; Kamlesh, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Total Knee Arthroplasty (TKA) is a common orthopedic procedure aimed at alleviating pain and restoring function in severely arthritic knee joints. With an increasing number of primary TKAs being performed, the number of revision surgeries has also risen. Understanding and comparing the complications associated with primary and revision TKA is crucial for improving surgical outcomes and patient care. Methods: This cross-sectional study analyzed 200 patients who underwent TKA, dividing them into two groups: those receiving primary TKA and those undergoing revision TKA. Data were collected retrospectively from medical records at a single tertiary care center, focusing on demographic information, surgical details, and postoperative complications. Statistical analysis was performed to compare the complication rates between the two groups. Results: The revision TKA group was older (average age 70 years) compared to the primary TKA group (average age 65 years), with a significant difference in age (P<0.05). Complication rates were higher in the revision TKA group, with infection rates at 11% compared to 7.5% in the primary group (P<0.01), mechanical failure rates at 9.5% versus 5.5% (P<0.01), and readmission rates at 15% against 9% (P<0.001). The severity of complications was also greater in the revision group, with a significant increase in moderate and severe complications. Conclusion: Revision TKA is associated with higher and more severe complications compared to primary TKA. These findings underscore the need for tailored perioperative strategies and enhanced patient selection to mitigate the risks associated with revision knee arthroplasty. Future research should focus on longitudinal studies to capture long-term outcomes and further refine surgical and management practices.